Three-dimensional graphene / metal oxide composite pellet as well as preparation method and application thereof

The described method for producing three-dimensional graphene/metal oxide composite microspheres addresses the challenge of achieving high surface area and stability, enhancing their application in gas sensing and energy storage.

CN119612593AActive Publication Date: 2025-03-14CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311168214.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-14
Estimated Expiration
2043-09-11

AI Technical Summary

Technical Problem

Current methods for preparing three-dimensional graphene/metal oxide composites fail to produce millimeter-scale materials with high surface area, leading to instability and limited applications in sensors due to uncontrolled shape and poor electrical performance.

Method used

A method involving the preparation of three-dimensional graphene/metal oxide composite microspheres through a two-step process, including the formation of graphene microspheres via ultrasonic dispersion and subsequent metal oxide loading via microwave-assisted hydrothermal treatment, resulting in microspheres with uniform metal oxide distribution and high surface area.

Benefits of technology

The resulting microspheres exhibit enhanced surface area and structural stability, enabling improved gas sensing, catalysis, and energy storage capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612593A_ABST
    Figure CN119612593A_ABST
Patent Text Reader

Abstract

The invention relates to the field of materials, and discloses a three-dimensional graphene / metal oxide composite pellet and a preparation method and application field thereof, the three-dimensional graphene / metal oxide composite pellet comprises a graphene pellet and a metal oxide loaded on the graphene pellet; wherein the specific surface area of the three-dimensional graphene / metal oxide composite sphere is 50-500m < 2 > / g. In the obtained three-dimensional graphene / metal oxide composite sphere, the metal oxide is uniformly loaded on the surface of the graphene sphere, and the sphere internally has a rich pore structure, so that the application of gas sensing, catalysis, energy storage and the like is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of materials, and in particular to a three-dimensional graphene / metal oxide composite pellet and a preparation method and application thereof. Background Art

[0002] In recent years, graphene, as a two-dimensional nanosheet material, has excellent performance. -1 ), thermal conductivity (thermal conductivity can reach 5300W·m -1 K -1 ), mechanical properties (Young's modulus reaches 1TPa) and large specific surface area (2630m 2 ·g -1 ) and extremely high light transmittance (absorbance is only 2.3%), which makes graphene applicable to many fields: preparation of conductive and thermal conductive composite materials, high-strength composite materials, catalytic electrode materials, aerogel materials, etc., becoming one of the hot spots in the research of nano gas-sensitive materials.

[0003] Common graphene materials can be divided into one-dimensional nanofibers, two-dimensional nanofilms, and three-dimensional graphene porous materials based on their dimensions. The porous structure of three-dimensional graphene is highly beneficial for improving its adsorption, energy storage, and gas-sensing properties. First, the three-dimensional structure effectively reduces the stacking of graphene sheets, which helps maintain graphene's high specific surface area and increases the number of active sites for reactions. Second, the interconnected pores facilitate the diffusion of molecules into the material, improving its sensitivity. Finally, the three-dimensional graphene skeleton not only provides support sites for the loading of other nanomaterials, but also accelerates the flow of electrons within the material, enhancing its conductivity. Nanometal oxides include nanoiron trioxide (Fe2O3), tin dioxide (SnO2), tungsten trioxide (WO3), molybdenum trioxide (MoO3), copper oxide (CuO), and zinc oxide (ZnO). Due to their unique crystal structure, morphology, composition, and physical and chemical properties, they have a wide range of applications in catalysis, energy storage, and sensing. Combining three-dimensional graphene with nano-metal oxides can achieve complementary advantages between the two, while further enhancing their performance and expanding their application range by utilizing heterojunctions and synergistic effects.

[0004] However, current methods for preparing three-dimensional graphene / metal oxide composites involve either directly adding nanometal oxides to a graphene oxide solution to form a three-dimensional structure through hydrothermal or chemical reduction methods, or directly adding a metal oxide precursor to a graphene oxide solution to simultaneously generate the metal oxide and form the three-dimensional structure. In the former, the metal oxide and graphene are connected only through physical interactions, resulting in poor stability and electrochemical properties. The latter, on the other hand, requires stringent reaction conditions for forming a three-dimensional structure and is only suitable for the composite of small amounts of metal oxides. Furthermore, the methods are complex, and the three-dimensional graphene / metal oxide composites prepared by both methods are mostly cylindrical in shape, making them difficult to assemble into sensor devices, which in turn affects the stability and electrical performance of the sensor devices. Millimeter-sized spherical three-dimensional graphene / metal oxide composites are rare. Summary of the Invention

[0005] The purpose of the present invention is to overcome the problem that the existing technology cannot prepare millimeter-scale three-dimensional graphene / metal oxide composite spheres with a high specific surface area, and to provide a three-dimensional graphene / metal oxide composite sphere and its preparation method and application. The three-dimensional graphene / metal oxide composite sphere has a rich pore structure inside, which is beneficial for applications such as gas sensing, catalysis, and energy storage.

[0006] In order to achieve the above object, the present invention provides a three-dimensional graphene / metal oxide composite sphere, wherein the three-dimensional graphene / metal oxide composite sphere comprises a graphene sphere and a metal oxide supported on the graphene sphere;

[0007] The specific surface area of ​​the three-dimensional graphene / metal oxide composite spheres is 50-500m 2 / g.

[0008] Preferably, the three-dimensional graphene / metal oxide composite spheres have a multi-level pore structure with an average pore diameter of 0.1-50 nm.

[0009] Preferably, the diameter of the three-dimensional graphene / metal oxide composite spheres is 0.5-5 mm.

[0010] Preferably, the metal oxide is selected from one or more of WO3, CuO, ZnO, Co3O4, MoO3 and SnO2.

[0011] A second aspect of the present invention provides a method for preparing the above-mentioned three-dimensional graphene oxide / metal oxide composite spheres, the preparation method comprising the following steps:

[0012] (1) mixing graphene oxide, sodium alginate and water, and then performing ultrasonication and heating to obtain a mixed dispersion;

[0013] (2) The mixed dispersion was dropped into the Ca 2+ soaking the graphene oxide / sodium alginate hydrogel in an aqueous solution to obtain graphene oxide / sodium alginate hydrogel, and washing the graphene oxide / sodium alginate hydrogel to obtain graphene oxide pellets;

[0014] (3) mixing the graphene oxide beads, metal salt and water to obtain a mixture;

[0015] (4) subjecting the mixture to a hydrothermal reaction, and then sequentially subjecting it to solid-liquid separation, washing, freeze-drying, and sintering.

[0016] Preferably, in step (1), the weight ratio of the graphene oxide, sodium alginate and water is 1-15:0.1-50:1000, preferably 5-10:0.1-40:1000.

[0017] Preferably, in step (1), the ultrasonication time is 10-120 min.

[0018] Preferably, in step (1), the heating conditions include: temperature of 70-95° C. and time of 3-6 h.

[0019] Preferably, in step (2), the flow rate of the injection pump is 10-200 μL / min.

[0020] Preferably, in step (2), the Ca 2+ Ca in aqueous solution 2+ The concentration is 1-10% by weight.

[0021] Preferably, in step (2), the soaking time is 1-24 hours.

[0022] Preferably, in step (2), the washing process comprises: rinsing the graphene oxide / sodium alginate hydrogel with water, and then soaking it in water for 12-48 hours.

[0023] Preferably, in step (3), the metal salt is selected from one or more of tungstate, copper salt, cobalt salt, zinc salt, molybdate and tin salt.

[0024] Preferably, the metal salt is selected from one or more of sodium tungstate, copper sulfate, zinc nitrate, cobalt nitrate, ammonium molybdate and stannous chloride.

[0025] Preferably, in step (3), the weight ratio of the graphene oxide beads, the metal salt and the water is 1:1-20:2000-2600.

[0026] Preferably, in step (4), the hydrothermal reaction is a microwave hydrothermal reaction.

[0027] Preferably, the conditions of the microwave hydrothermal reaction include: temperature of 150-220° C., time of 0.5-6 h, and microwave power of 400-800 W.

[0028] Preferably, in step (4), the freeze-drying conditions include: temperature of 25-60°C and time of 12-48h.

[0029] Preferably, in step (4), the sintering conditions are: temperature of 200-700° C., time of 1-5 h, and inert atmosphere.

[0030] A third aspect of the present invention provides an application of the above-mentioned three-dimensional graphene / metal oxide composite spheres in the fields of gas sensing, adsorption or energy storage.

[0031] This method uses a two-step process to prepare three-dimensional graphene / metal oxide composite spheres. First, graphene oxide millispheres are prepared by microinjection. Metal salts are then mixed with the graphene oxide millispheres. The resulting three-dimensional graphene / metal oxide composite spheres are then subjected to microwave-assisted hydrothermal treatment, freeze-drying, and high-temperature sintering. The metal oxide is uniformly loaded on the surface of the graphene spheres, and the spheres have a rich pore structure within them, which is beneficial for applications such as gas sensing, catalysis, and energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is an optical scanning photo of a three-dimensional graphene / WO3 composite sphere;

[0033] Figure 2 This is a picture of the nitrogen adsorption and desorption performance of three-dimensional graphene / WO3 composite spheres;

[0034] Figure 3 This is a scanning electron microscope image of three-dimensional graphene / WO3 composite spheres;

[0035] Figure 4 These are scanning electron microscope images of three-dimensional graphene / CuO composite pellets and freeze-dried pellets. DETAILED DESCRIPTION

[0036] The following describes the specific embodiments of the present invention in detail with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention.

[0037] The endpoints of the ranges and any values ​​disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.

[0038] In one aspect, the present invention provides a three-dimensional graphene / metal oxide composite sphere, wherein the three-dimensional graphene / metal oxide composite sphere comprises a graphene sphere and a metal oxide supported on the graphene sphere;

[0039] The specific surface area of ​​the three-dimensional graphene / metal oxide composite spheres is 50-500m 2 / g.

[0040] Preferably, the three-dimensional graphene / metal oxide composite spheres have a multi-level pore structure with an average pore diameter of 0.1-50 nm, for example, 0.1 nm, 1 nm, 5 nm, 20 nm, 30 nm, 40 nm or 50 nm.

[0041] Preferably, the diameter of the three-dimensional graphene / metal oxide composite spheres is 0.5-5 mm.

[0042] In the present invention, in order to make the three-dimensional graphene / metal oxide composite spheres have better gas sensing performance, it is also necessary to control the specific surface area of ​​the three-dimensional graphene / metal oxide composite spheres within the above range in a preferred embodiment. In a specific embodiment, the specific surface area of ​​the three-dimensional graphene / metal oxide composite spheres can be 50m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g、350m 2 / g or 500m 2 / g.

[0043] Preferably, the metal oxide is selected from one or more of WO3, CuO, ZnO, Co3O4, MoO3 and SnO2.

[0044] A second aspect of the present invention provides a method for preparing the above-mentioned three-dimensional graphene oxide / metal oxide composite spheres, the preparation method comprising the following steps:

[0045] (1) mixing graphene oxide, sodium alginate and water, and then performing ultrasonication and heating to obtain a mixed dispersion;

[0046] (2) The mixed dispersion was dropped into the Ca 2+ soaking the graphene oxide / sodium alginate hydrogel in an aqueous solution to obtain graphene oxide / sodium alginate hydrogel, and washing the graphene oxide / sodium alginate hydrogel to obtain graphene oxide pellets;

[0047] (3) mixing the graphene oxide beads, metal salt and water to obtain a mixture;

[0048] (4) subjecting the mixture to a hydrothermal reaction, and then sequentially subjecting it to solid-liquid separation, washing, freeze-drying, and sintering.

[0049] In the present invention, graphene oxide, as the single-layer material peeled off from graphite oxide, can stably exist in aqueous solution and polar solvent due to the introduction of a large amount of oxygen-containing groups on the surface and edge.After oxidation treatment, graphite oxide still keeps the layered structure of graphite, but has introduced many oxygen-based functional groups on the graphene monolith of each layer.The introduction of these oxygen-based functional groups makes single graphene structure become very complicated.In view of the status of graphene oxide in the field of graphene materials, many scientists attempt to describe the structure of graphene oxide in detail and accurately, so that are conducive to the further research of graphene materials, although have utilized computer simulation, Raman spectroscopy, means such as nuclear magnetic resonance are analyzed its structure, but due to various reasons (different preparation methods, the difference of experimental conditions and different graphite sources all have a certain impact on the structure of graphene oxide), the accurate structure of graphene oxide can't be determined. The generally accepted structural model is that hydroxyl and epoxy groups are randomly distributed on the graphene oxide monolith, while carboxyl and carbonyl groups are introduced at the edges of the monolith. However, relevant theoretical analysis shows that the surface functional groups of graphene oxide are not randomly distributed, but are highly correlated.

[0050] Sodium alginate is a byproduct of extracting iodine and mannitol from brown algae such as kelp or sargassum. Its molecule is composed of β-D-mannuronic acid (β-D-mannuronic, M) and α-L-guluronic acid (α-L-guluronic, G) connected by (1→4) bonds. The aqueous solution of sodium alginate has a high viscosity and is easy to form a gel under mild conditions. When there is Ca 2+ 、Sr 2+ In the presence of cations, the Na + Ion exchange reaction occurs with divalent cations, and the G units stack to form a cross-linked network structure, thereby forming a hydrogel.

[0051] In the preparation method of the present invention, in order to facilitate the formation of graphene / sodium alginate hydrogel and obtain graphene spheres with better performance, it is necessary to reasonably control the amount of graphene oxide, sodium alginate and water. The addition of sodium alginate can increase the viscosity and strength of the dispersion and prevent the dispersion from dripping from the syringe pump to the Ca 2+ When in solution, it deforms due to low strength; however, the amount of sodium alginate should not be too high. Too much sodium alginate will cause the viscosity of the dispersion to be too high and clog the injection pump.

[0052] Therefore, in a preferred embodiment, in step (1), the weight ratio of the graphene oxide, sodium alginate and water is 1-15:0.1-50:1000, and more preferably 5-10:0.1-40:1000.

[0053] In a specific embodiment, in step (1), the weight ratio of the graphene oxide to water can be 5:1000, 6:1000, 7:1000, 8:1000, 9:100 or 10:1000, and the weight ratio of the sodium alginate to water can be 0.1:1000, 1:1000, 5:1000, 10:1000, 15:1000, 20:1000, 25:1000, 30:1000, 35:1000 or 40:1000.

[0054] In the method of the present invention, in step (1), since the viscosity of the entire system increases upon addition of sodium alginate, it is necessary to completely disperse the graphene oxide by ultrasound, and the ultrasound time can be adjusted according to the amount of sodium alginate added. Preferably, in step (1), the ultrasound time is 10-120 minutes, specifically 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes, or 120 minutes.

[0055] In the present invention, in step (1), the heating operation can completely dissolve the sodium alginate and prevent agglomeration, and the heating time is related to the amount of sodium alginate added. In a preferred embodiment, the heating conditions include: a temperature of 70-95° C. and a time of 3-6 hours.

[0056] In a specific embodiment, in step (1), the heating temperature can be 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, and the heating time can be 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h.

[0057] Preferably, in step (2), in step (2), the flow rate of the injection pump is 10-200 μL / min, specifically 10 μL / min, 30 μL / min, 50 μL / min, 70 μL / min, 90 μL / min, 110 μL / min, 130 μL / min, 150 μL / min, 180 μL / min or 200 μL / min.

[0058] In the method described in the present invention, in step (2), the Ca 2+ In aqueous solution, if Ca 2+ If the concentration of Ca is too low, the strength of the gel will be too low. 2+ If the concentration of Ca is too high, too much will remain in the gel, affecting the structure and performance. Therefore, in a preferred embodiment, preferably, in step (2), the Ca 2+ Ca in aqueous solution 2+ The concentration of the compound is 1-10% by weight, specifically 1% by weight, 2% by weight, 3% by weight, 4% by weight, 5% by weight, 6% by weight, 7% by weight, 8% by weight, 9% by weight or 10% by weight.

[0059] In the method of the present invention, the Ca 2+ The aqueous solution can be obtained by mixing various water-soluble calcium salts commonly used in the art with water. In a specific embodiment, the calcium-containing 2+ The aqueous solution is a calcium chloride aqueous solution.

[0060] In step (2) of the present invention, the Ca 2+ There is no special requirement for the amount of the aqueous solution used, as long as it can completely soak the mixed dispersion dripped by the injection pump.

[0061] In the method of the present invention, in step (2), the soaking time is counted from the completion of the dropwise addition to the end of the soaking. Preferably, in step (2), the soaking time is 1-24 hours, more preferably 6-24 hours. Specifically, the soaking time can be 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 2 hours or 24 hours.

[0062] In the method of the present invention, in order to fully remove calcium ions from the hydrogel, the product can be washed by rinsing and soaking. Therefore, in step (2), preferably, the washing process includes: rinsing the graphene oxide / sodium alginate hydrogel with water, and then soaking it in water for 12-48 hours. The specific soaking time can be 12 hours, 16 hours, 18 hours, 20 hours, 24 hours, 30 hours, 32 hours, 36 hours, 40 hours or 48 hours.

[0063] Preferably, in step (2), the number of rinses during the washing process is 1-5 times, specifically 1 time, 2 times, 3 times, 4 times or 5 times.

[0064] In step (3) of the present invention, the metal salt is selected from one or more of tungstates, copper salts, cobalt salts, zinc salts, molybdates and tin salts, and is more preferably a soluble salt.

[0065] In a preferred embodiment of the present invention, the tungstate is used to provide tungsten element and can be a soluble tungstate commonly used in the art, for example, one or more of potassium tungstate, sodium tungstate and ammonium tungstate.

[0066] In a preferred embodiment of the present invention, the copper salt is used to provide the copper element and can be a soluble copper salt commonly used in the art, for example, one or more of copper chloride, copper sulfate and copper nitrate.

[0067] In a preferred embodiment of the present invention, the cobalt salt is used to provide the cobalt element and can be a soluble cobalt salt commonly used in the art, for example, one or more of cobalt chloride, cobalt carbonate, cobalt sulfate and cobalt nitrate.

[0068] In a preferred embodiment of the present invention, the zinc salt is used to provide zinc element and can be a soluble zinc salt commonly used in the art, for example, one or more of zinc chloride, zinc sulfate and zinc nitrate.

[0069] In a preferred embodiment of the present invention, the molybdate is used to provide the molybdenum element and can be a soluble molybdate commonly used in the art, for example, one or more of potassium molybdate, ammonium molybdate and sodium molybdate.

[0070] In a preferred embodiment of the present invention, the tin salt is used to provide the tin element and can be a soluble tin salt commonly used in the art.

[0071] Preferably, in step (3), the metal salt is selected from one or more of sodium tungstate, copper sulfate, zinc nitrate, cobalt nitrate, ammonium molybdate and stannous chloride.

[0072] Preferably, in step (3), the weight ratio of the graphene oxide beads, the metal salt and the water is 1:1-20:2000-2600.

[0073] In a specific embodiment of step (3), the weight ratio of the graphene oxide spheres to the metal salt can be 1:1, 1:5, 1:10, 1:15 or 1:20, and the weight ratio of the graphene oxide spheres to water is 1:2000, 1:2100, 1:2200, 1:2300, 1:2400, 1:2500 or 1:2600.

[0074] In step (3) of the present invention, due to the different metal salts used, a certain amount of acid or base needs to be added to adjust the pH value to an appropriate range to form a stably dispersed hydrosol, thereby ensuring uniform growth of nano-metal oxides during the heating process.

[0075] Therefore, in a specific embodiment of the present invention, when the metal salt is sodium tungstate, the specific process of step (3) includes: mixing the graphene oxide beads, the metal salt and water, and then adding a hydrochloric acid solution with a concentration of 2 mol / L dropwise under stirring, adjusting the pH value to 1.5-2.5, and then obtaining a mixture, wherein the addition time of the hydrochloric acid solution is controlled to be 10-30 min; wherein there is no special requirement for the dropping speed of the hydrochloric acid solution, and the addition can be completed within the specified time.

[0076] In a specific embodiment of the present invention, when the metal salt is copper sulfate, the specific process of step (3) includes: mixing the graphene oxide beads, the metal salt and water, then adding a sodium hydroxide solution with a concentration of 2 mol / L dropwise under stirring, adjusting the pH value to 9.5-10.5, and then obtaining a mixture, wherein the sodium hydroxide solution is added dropwise for 10-30 min; wherein there is no special requirement for the dropping speed of the sodium hydroxide solution, and the addition can be completed within a limited time.

[0077] In a specific embodiment of the present invention, when the metal salt is zinc nitrate, the specific process of step (3) includes: mixing the graphene oxide beads, the metal salt and water, then adding a sodium hydroxide solution with a concentration of 2 mol / L dropwise under stirring, adjusting the pH value to 9.5-10.5, and then obtaining a mixture, wherein the sodium hydroxide solution is added dropwise for 10-30 min; wherein there is no special requirement for the dropping speed of the sodium hydroxide solution, and the addition can be completed within a limited time.

[0078] In a specific embodiment of the present invention, when the metal salt is cobalt nitrate, the specific process of step (3) includes: mixing the graphene oxide beads, the metal salt and water, then adding a 2 mol / L sodium hydroxide solution dropwise under stirring to adjust the pH value to 9.5-10.5, and then obtaining a mixture, wherein the sodium hydroxide solution is added dropwise for 10-30 min; wherein there is no special requirement for the dropping speed of the sodium hydroxide solution, and the addition can be completed within a limited time.

[0079] In a specific embodiment of the present invention, when the metal salt is ammonium molybdate, the specific process of step (3) includes: mixing the graphene oxide beads, the metal salt and water, then adding a nitric acid solution with a concentration of 2 mol / L dropwise under stirring, adjusting the pH value to 1.5-2.5, and then obtaining a mixture, wherein the addition time of the nitric acid solution is controlled to be 10-30 min; wherein there is no special requirement for the dropping speed of the nitric acid solution, and the addition can be completed within a limited time.

[0080] In a specific embodiment of the present invention, when the metal salt is stannous chloride, stannous chloride can hydrolyze by itself and form a stably dispersed aqueous sol, so there is no need to add acid or alkali. Therefore, when the metal salt is stannous chloride, the specific process of step (3) includes: mixing the graphene oxide beads, the metal salt and water, and then stirring for 10-30 minutes to obtain a mixture.

[0081] In a specific embodiment of the present invention, in step (3), when sodium hydroxide solution, hydrochloric acid solution or nitric acid solution is added, the amount of water used is calculated based on the total amount of water added and the water contained in the added solution. When the water content in the added sodium hydroxide solution, hydrochloric acid solution or nitric acid solution meets the required ratio of the amounts of graphene oxide beads, metal salt and water, no additional water may be added.

[0082] In a preferred embodiment, in step (4), the hydrothermal reaction is a microwave hydrothermal reaction. The use of a microwave hydrothermal method is conducive to obtaining nanomaterials with more uniform size distribution, improving the stability of the material, and greatly shortening the reaction time.

[0083] Preferably, the conditions of the microwave hydrothermal reaction include: temperature of 150-220° C., time of 0.5-6 h, and microwave power of 400-800 W.

[0084] In a specific embodiment of step (4), the temperature of the microwave hydrothermal reaction can be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C or 220°C, the time of the microwave hydrothermal reaction can be 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h, and the microwave power can be 400W, 500W, 600W, 700W or 800W.

[0085] In a preferred embodiment, in step (4), when washing the solid phase obtained by solid-liquid separation, anhydrous ethanol and deionized water are used in sequence.

[0086] More preferably, the number of times of washing with anhydrous ethanol is 2-5 times, and the number of times of washing with deionized water is 2-5 times.

[0087] In the method of the present invention, freeze-drying in step (4) can prevent the pore structure of the gel from collapsing, thereby preserving the three-dimensional structure of the spheres to the greatest extent.

[0088] Therefore, preferably, in step (4), the freeze-drying conditions include: temperature of 25-60°C and time of 12-48h.

[0089] In a specific embodiment of step (4), the freeze-drying temperature can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C, and the freeze-drying time can be 12h, 18h, 24h, 30h, 36h, 42h or 48h.

[0090] In step (4) of the present invention, the sintering operation can remove sodium alginate on the one hand, and reduce graphene oxide on the other hand, thereby improving its electrical conductivity and mechanical properties, while also improving the crystal structure of the metal oxide.

[0091] Therefore, preferably, in step (4), the sintering conditions are: temperature of 200-700°C, time of 1-5h, and inert atmosphere. Specifically, the sintering temperature can be 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C, and the sintering time can be 1h, 2h, 3h, 4h or 5h.

[0092] Further preferably, in step (4), the inert atmosphere can be provided by one or more gases selected from the group consisting of nitrogen, helium, neon, argon, krypton and xenon.

[0093] A third aspect of the present invention provides an application of the above-mentioned three-dimensional graphene / metal oxide composite spheres in the fields of gas sensing, adsorption or energy storage.

[0094] Compared with the existing technology, the beneficial effects of this patent are mainly:

[0095] 1. The obtained three-dimensional graphene / metal oxide composite spheres have controllable size and structure and a high specific surface area;

[0096] 2. The metal oxides are evenly dispersed on the surface of the spheres and can be used to prepare gas-sensitive materials, adsorption materials, and electrode materials.

[0097] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.

[0098] The room temperature below refers to 25℃.

[0099] Example 1

[0100] (1) Disperse 50 mg of graphene oxide in 10 ml (10 g) of deionized water, add 0.1 g of sodium alginate, and stir evenly, i.e., the weight ratio of graphene oxide, sodium alginate, and deionized water is 5:10:1000; then ultrasonicate for 30 min to completely exfoliate the graphene oxide sheets and evenly disperse them in water, and then heat at 70 ° C for 4 h to obtain a mixed dispersion;

[0101] (2) Add the mixed dispersion to the microinjection pump and control the flow rate of the injection pump to 30uL / min so that the mixed dispersion droplets fall evenly on the calcium chloride aqueous solution (Ca 2+ The graphene oxide / sodium alginate hydrogel was rinsed with deionized water three times and then soaked in deionized water for 24 hours to obtain graphene oxide pellets;

[0102] (3) 0.1 g of graphene oxide beads were added to a 500 mL beaker, followed by 190 mL (190 g) of deionized water, followed by 1.06 g of sodium tungstate, and a 2 mol / L hydrochloric acid solution was added dropwise at room temperature and under stirring to adjust the pH value to 2. The addition time of the hydrochloric acid solution was controlled to be 30 min to obtain a mixture, wherein the weight ratio of the graphene oxide beads, sodium tungstate and water was 1:10.6:2400 (the amount of water at this time was the amount of deionized water plus the water content in the hydrochloric acid solution). At this time, the mixture was a uniform suspension;

[0103] (4) The mixture was transferred to a hydrothermal reactor and then placed in a microwave synthesizer. Microwave (microwave power 800 W) assisted hydrothermal treatment was performed at 180 °C for 0.5 h. After naturally cooling to room temperature, the solid obtained by solid-liquid separation was washed three times with anhydrous ethanol and deionized water respectively, and then freeze-dried at 25 °C for 24 h to obtain freeze-dried pellets. The pellets were then sintered at 500 °C for 2 h under nitrogen protection to obtain three-dimensional graphene / WO3 composite pellets.

[0104] Example 2

[0105] The method of Example 1 was followed, except that step (3) was as follows: 0.1 g of graphene oxide spheres were added to a 500 mL beaker, followed by the addition of 220 mL (220 g) of deionized water, followed by the addition of 0.55 g of copper sulfate, and a 2 mol / L sodium hydroxide solution was added dropwise at room temperature with stirring, the pH value was adjusted to 10, and the addition time of the sodium hydroxide solution was controlled to be 30 min, to obtain a mixture, wherein the weight ratio of the graphene oxide spheres, copper sulfate, and water was 1:5.5:2400 (the amount of water in this case was the amount of deionized water plus the water content in the sodium hydroxide solution); and finally, three-dimensional graphene / CuO composite spheres were obtained.

[0106] Example 3

[0107] The method of Example 1 was followed, except that step (3) was as follows: 0.1 g of graphene oxide spheres were added to a 500 mL beaker, 220 mL (220 g) of deionized water was added, and then 1.428 g of zinc nitrate was added dropwise at room temperature with stirring. A 2 mol / L sodium hydroxide solution was added, the pH value was adjusted to 10, and the addition time of the sodium hydroxide solution was controlled to be 30 min. Then, a mixture was obtained, in which the weight ratio of the graphene oxide spheres, zinc nitrate, and water was 1:14.28:2400 (the amount of water in this case was the amount of deionized water plus the water content in the sodium hydroxide solution); and finally, three-dimensional graphene / ZnO composite spheres were obtained.

[0108] Example 4

[0109] The method of Example 1 was followed, except that step (3) was as follows: 0.1 g of graphene oxide spheres were added to a 500 mL beaker, 220 mL (220 g) of deionized water was added, and then 1.164 g of cobalt nitrate was added. A 2 mol / L sodium hydroxide solution was added dropwise at room temperature with stirring, the pH value was adjusted to 10, and the addition time of the sodium hydroxide solution was controlled to be 30 min. Then, a mixture was obtained, in which the weight ratio of the graphene oxide spheres, cobalt nitrate and water was 1:11.64:2400 (the amount of water in this case was the amount of deionized water plus the water content in the sodium hydroxide solution); and finally, three-dimensional graphene / Co3O4 composite spheres were obtained.

[0110] Example 5

[0111] The method of Example 1 was followed, except that step (3) was as follows: 0.1 g of graphene oxide spheres were added to a 500 mL beaker, followed by the addition of 220 mL (220 g) of deionized water, followed by the addition of 1.76 g of ammonium molybdate, and a 2 mol / L nitric acid solution was added dropwise at room temperature with stirring, the pH value was adjusted to 2, and the addition time of the nitric acid solution was controlled to be 30 min, to obtain a mixture, wherein the weight ratio of the graphene oxide spheres, ammonium molybdate and water was 1:17.6:2400 (the amount of water at this time was the amount of deionized water plus the water content in the nitric acid solution); and finally, three-dimensional graphene / MoO3 composite spheres were obtained.

[0112] Example 6

[0113] The method of Example 1 was followed, except that step (3) was as follows: 0.1 g of graphene oxide spheres were added to a 500 mL beaker, followed by adding 240 mL (240 g) of deionized water, followed by adding 1.2 g of stannous chloride, i.e., the weight ratio of graphene oxide spheres, stannous chloride, and deionized water was 1:12:2400, and the mixture was stirred at room temperature for 30 min to obtain a mixture; and finally, three-dimensional graphene / SnO2 composite spheres were obtained.

[0114] Example 7

[0115] The method of Example 1 is implemented, except that the operation of step (1) is:

[0116] 50 mg of graphene oxide was dispersed in 5 mL of deionized water, 0.1 g of sodium alginate was added, and the mixture was stirred evenly, i.e., the weight ratio of graphene oxide, sodium alginate, and water was 10:20:1000. The mixture was then ultrasonicated for 100 minutes to completely exfoliate the graphene oxide sheets and evenly disperse them in water. The mixture was then heated at 70°C for 4 hours to obtain a mixed dispersion. Finally, three-dimensional graphene / WO3 composite spheres were obtained.

[0117] Example 8

[0118] The method of Example 1 is implemented, except that the operation of step (2) is:

[0119] Add the mixed dispersion to the microinjection pump and control the flow rate of the injection pump to 100uL / min, so that the mixed dispersion drops evenly fall on the calcium chloride aqueous solution (Ca 2+ The graphene oxide / sodium alginate hydrogel was rinsed with deionized water three times and then soaked in deionized water for 24 hours to obtain graphene oxide spheres; and finally, three-dimensional graphene / WO3 composite spheres were obtained.

[0120] Example 9

[0121] The method of Example 1 is implemented, except that the operation of step (4) is:

[0122] The mixture was transferred to a hydrothermal kettle and then placed in a microwave synthesizer. Microwave (microwave power 800W) assisted hydrothermal treatment was performed at 200°C for 3 hours. After naturally cooling to room temperature, the solid obtained by solid-liquid separation was washed three times with anhydrous ethanol and deionized water respectively, and then freeze-dried at 50°C for 24 hours. Then, it was sintered at 500°C for 4 hours under nitrogen protection to obtain three-dimensional graphene / WO3 composite spheres.

[0123] Example 10

[0124] The method of Example 1 was followed, except that in step (4), the sintering temperature was 200° C. to obtain three-dimensional graphene / WO 3 composite pellets.

[0125] Comparative Example 1

[0126] The method of Example 1 was followed, except that step (3) was as follows: 0.1 g of graphene oxide pellets were added to a 500 mL beaker, followed by 240 mL of deionized water, and then 0.5 g of WO3 were added. The mixture was stirred at room temperature for 30 min, and then a mixture was obtained; finally, three-dimensional graphene / WO3 composite pellets were obtained.

[0127] Comparative Example 2

[0128] The method of Comparative Example 1 was followed, except that WO3 was replaced with CuO of the same weight, to finally obtain three-dimensional graphene / CuO composite beads.

[0129] Comparative Example 3

[0130] The method of Comparative Example 1 was followed, except that WO3 was replaced with ZnO of equal weight, to finally obtain three-dimensional graphene / ZnO composite beads.

[0131] Comparative Example 4

[0132] The method of Comparative Example 1 was followed, except that WO3 was replaced by Co3O4 of equal weight, to finally obtain three-dimensional graphene / Co3O4 composite beads.

[0133] Comparative Example 5

[0134] The method of Comparative Example 1 was followed, except that WO3 was replaced with MoO3 of equal weight, to finally obtain three-dimensional graphene / MoO3 composite pellets.

[0135] Test Example 1

[0136] The morphology of the graphene / metal oxide composite spheres obtained in Examples 1-10 and Comparative Examples 1-5 was tested using a scanning electron microscope. The results are shown in Table 1. The morphology of the graphene / WO3 composite spheres obtained in Example 1 is shown in Table 1. Figure 1 As shown, from Figure 1 It can be seen that the obtained graphene / WO3 composite balls are uniformly spherical with a diameter of 1.78 mm.

[0137] Test Example 2

[0138] The specific surface area and pore structure of the graphene / metal oxide composite beads obtained in Examples 1-10 and Comparative Examples 1-5 were tested by nitrogen adsorption and desorption method (i.e., BET method). The results are shown in Table 1. The graphene / WO3 composite beads obtained in Example 1 are as follows: Figure 2 As shown, from Figure 2 It can be seen that the specific surface area of ​​the graphene / WO3 composite sphere is 206m 2 / g, has a very high specific surface area, and has multi-level pores ranging from 2 nanometers to 100 nanometers, with an average pore diameter of 10.38 nm.

[0139] Table 1

[0140]

[0141]

[0142] Test Example 3

[0143] The morphology of the graphene / WO3 composite spheres obtained in Example 1 was tested using a scanning electron microscope. Figure 3 As shown, from Figure 3 It can be seen that WO3 nanosheets are successfully loaded on the surface of graphene spheres through the in-situ loading method and the WO3 nanosheets are evenly distributed on the surface of graphene spheres.

[0144] Test Example 4

[0145] The morphology of the three-dimensional graphene / CuO composite pellets obtained in Example 2 and the freeze-dried pellets obtained after freeze-drying were tested using a scanning electron microscope. Figure 4 As shown, Figure 4 B1, B2, and B3 are pictures of three-dimensional graphene / CuO composite beads, and A1, A2, and A3 are pictures of freeze-dried beads. Figure 4It can be seen that the material grown on the surface of the freeze-dried beads is CuO nanorod clusters with a length of about 500nm. After sintering at 500℃, the CuO nanorods disappear and crystal particles with a size of about 1um appear. At the same time, a large number of CuO particles with a size of about 50nm are evenly distributed on the surface of the graphene beads, indicating that the high temperature sintering treatment in the present invention is beneficial to improving the crystallinity of nano-oxides and improving the gas-sensitive response effect of three-dimensional graphene / metal oxide composite beads.

[0146] The above results show that the three-dimensional graphene / metal oxide composite spheres obtained in the present invention have a high specific surface area and abundant nanopores, which are conducive to the surface adsorption of gas and liquid molecules and promote the transmission of gas and liquid molecules in the internal pores. At the same time, the surface of the composite material has a large number of active sites, which can accelerate the physical and chemical reactions on the surface and can be widely used in gas sensing, adsorption or energy storage fields.

[0147] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.

Claims

1. A three-dimensional graphene / metal oxide composite sphere, characterized in that: The three-dimensional graphene / metal oxide composite spheres include graphene spheres and metal oxides supported on the graphene spheres; The specific surface area of ​​the three-dimensional graphene / metal oxide composite sphere is 50-500m 2 / g.

2. The three-dimensional graphene / metal oxide composite sphere according to claim 1, characterized in that: The three-dimensional graphene / metal oxide composite spheres have a multi-level pore structure with an average pore diameter of 0.1-50 nm; Preferably, the diameter of the three-dimensional graphene / metal oxide composite sphere is 0.5-5 mm.

3. The three-dimensional graphene oxide / metal oxide composite sphere according to claim 1 or 2, characterized in that: The metal oxide is selected from one or more of WO3, CuO, ZnO, Co3O4, MoO3 and SnO2.

4. The method for preparing the three-dimensional graphene oxide / metal oxide composite beads according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing graphene oxide, sodium alginate and water, and then performing ultrasound and heating to obtain a mixed dispersion; (2) The mixed dispersion was dropped into a solution containing Ca by a syringe pump. 2+ soaking the graphene oxide / sodium alginate hydrogel in an aqueous solution to obtain graphene oxide / sodium alginate hydrogel, and washing the graphene oxide / sodium alginate hydrogel to obtain graphene oxide spheres; (3) mixing the graphene oxide beads, metal salt and water to obtain a mixture; (4) subjecting the mixture to a hydrothermal reaction, and then sequentially subjecting the mixture to solid-liquid separation, washing, freeze-drying and sintering.

5. The preparation method according to claim 4, characterized in that: In step (1), the weight ratio of the graphene oxide, sodium alginate and water is 1-15:0.1-50:1000, preferably 5-10:0.1-40:1000.

6. The preparation method according to claim 4 or 5, characterized in that: In step (1), the ultrasonication time is 10-120 min.

7. The preparation method according to claim 4, characterized in that: In step (1), the heating conditions include: temperature of 70-95°C and time of 3-6h.

8. The preparation method according to claim 4, characterized in that: In step (2), in step (2), the flow rate of the syringe pump is 10-200 μL / min.

9. The preparation method according to claim 4 or 8, characterized in that: In step (2), the Ca 2+ Ca in aqueous solution 2+ The concentration is 1-10% by weight.

10. The preparation method according to claim 4, characterized in that: In step (2), the soaking time is 1-24 hours.

11. The preparation method according to claim 4 or 10, characterized in that: In step (2), the washing process includes: rinsing the graphene oxide / sodium alginate hydrogel with water, and then soaking it in water for 12-48 hours.

12. The preparation method according to claim 4, characterized in that: In step (3), the metal salt is selected from one or more of tungstate, copper salt, cobalt salt, zinc salt, molybdate and tin salt; Preferably, it is selected from one or more of sodium tungstate, copper sulfate, zinc nitrate, cobalt nitrate, ammonium molybdate and stannous chloride.

13. The preparation method according to claim 4 or 12, characterized in that: In step (3), the weight ratio of the graphene oxide beads, the metal salt and the water is 1:1-20:2000-2600.

14. The preparation method according to claim 4, characterized in that: In step (4), the hydrothermal reaction is a microwave hydrothermal reaction; Preferably, the conditions of the microwave hydrothermal reaction include: temperature of 150-220° C., time of 0.5-6 h, and microwave power of 400-800 W.

15. The preparation method according to claim 4, characterized in that: In step (4), the freeze-drying conditions include: temperature of 25-60°C and time of 12-48h.

16. The preparation method according to claim 4, characterized in that: In step (4), the sintering conditions are: temperature of 200-700° C., time of 1-5 h, and inert atmosphere.

17. Application of the three-dimensional graphene / metal oxide composite beads as described in any one of claims 1 to 3 or the three-dimensional graphene / metal oxide composite beads prepared by the preparation method as described in any one of claims 4 to 16 in the field of gas sensing, adsorption or energy storage.

Citation Information

Patent Citations

  • Graphene composite material, and preparation methods and application thereof

    CN106531975A

  • Graphene oxide / sodium alginate composite microsphere as well as preparation method and application thereof

    CN107583624A

  • Metal oxide / three-dimensional porous graphene composite material and preparation method and application thereof

    CN107946084A

  • Quick and controllable preparation method of three-dimensional graphene microspheres for adsorption

    CN109896519A

  • Metal oxide / graphene nano-structure material prepared in microwave-assisted manner, and preparation method thereof

    CN111039283A

Cited By

  • Spherical powder material as well as preparation method and application thereof

    CN122035843A